2015
DOI: 10.1016/j.proci.2014.06.083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of segregation and bifurcation in turbulent spray flames: A 3D counterflow configuration

Abstract: International audienceThe understanding of spray combustion processes is of primary importance, as it is encountered in a wide range of industrial applications. In the present work, mesoscale-resolved simulations of a 3D turbulent counterflow spray configuration are conducted. Primary focus is on examining the effect of the coupling between turbulence, evap- oration, mixing, and combustion. By considering different initial droplet diameters and through comparisons with turbulent and laminar configurations at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…10(b) as long as the strain rate remains below 350 s −1 . This type of bifurcation was also observed in [23], where two branches were identified without the occurrence of an hysteresis 1 . It may also be noted that the temperature is overestimated for the highest values of the strain rate when solving the system in η-space.…”
Section: Effect Of Droplet Diameter and Strain Rate: Bifurcation And supporting
confidence: 63%
See 3 more Smart Citations
“…10(b) as long as the strain rate remains below 350 s −1 . This type of bifurcation was also observed in [23], where two branches were identified without the occurrence of an hysteresis 1 . It may also be noted that the temperature is overestimated for the highest values of the strain rate when solving the system in η-space.…”
Section: Effect Of Droplet Diameter and Strain Rate: Bifurcation And supporting
confidence: 63%
“…For all three cases considered, the first temperature peak is located on the gas side at stoichiometric condition. However, with increasing initial droplet diameter, a second temperature peak is formed on the spray side, which identifies the transition from a single-reaction to a double-reaction flame structure for large droplets, as observed in [16,23]. Moreover, by comparing profiles of Z g and Z l with the analytic solution, the diffusive contribution on the spray side can be clearly recognized.…”
Section: Effects Of Droplet Diameter On Spray-flame Structuresupporting
confidence: 53%
See 2 more Smart Citations
“…Most of them are on a simplified counterflow configuration, including early studies by Continillo and Sirignano [4] , Gutheil and Sirignano [9] , and more recently by Olguin and Gutheil [10] . Vié et al [11] performed a DNS study of a 3D spray counterflow configuration. It was found that the structure is strongly related to droplet size and strain rate.…”
Section: Introductionmentioning
confidence: 99%